Severity Level and Quality of Life of Post-Acute Coronary Syndrome Patients - Donny Nurhamsyah; Yanny Trisyani; Aan Nuraeni; Nur Maziyya (Jurnal Keperawatan Padjadjaran, 2021)
Background: Severity level is one of the variables used to determine the treatments of acute coronary syndrome patients. There are many ways to see the success of treatment such as measuring the patient’s quality of life. Purpose: This study aims to determine the correlation between severity level and quality of life among patients with post-acute coronary syndrome at Hasan Sadikin Central Hospital Bandung. Methods: This research was a quantitative study with a descriptive-analytic approach. Sampling of 100 patients with post-acute coronary syndrome patients was collected during a period of one month using consecutive sampling technique. The severity was assessed based on the stenosis number and the quality of life data were collected using the MacNew QLMI. Somers’d Gamma was used to analyze the data. Results: Data showed that most of the patients had angina without stenosis (36%) and coronary 1 stenosis (29%). The results of the quality of life measurement show that 58% patients have a good quality of life, 64% are good in the emotional domain, 52% are good in the physical domain, and 60% are good in the social domain. Bivariate analysis (CI 95%) showed that there was a significant correlation between severity level and quality of life (p-value 0.033), as well as with the physical domain (p-value 0,008). Conclusion: There is a correlation between severity level and quality of life of post-acute coronary syndrome patients in Hasan Sadikin Central Hospital Bandung. Based on the quality of life domain, the severity level was significantly related to the physical-domain. Regular screening is necessary to improve the quality of life of post-acute coronary syndrome patients.